2011
DOI: 10.4261/1305-3825.dir.4410-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of amplatzer® vascular plug 4

Abstract: The purpose of this study was to present our initial experience with the Amplatzer ® Vascular Plug (AVP) 4 in various arterial environments. This material was designed for the embolization of peripheral small vessels using a diagnostic catheter. Herein, the following three procedures using the AVP 4 were described: hemodialysis fistula occlusion as a treatment for the steal phenomenon, gastroduodenal artery embolization prior to liver radioembolization, and vertebral artery embolization for the treatment of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…We prefer the AVP 4 over AVP 1. This new device can be deployed through a 4 F diagnostic catheter, which is a major advantage of this device, especially in pediatric populations (12). However, it was not available at our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…We prefer the AVP 4 over AVP 1. This new device can be deployed through a 4 F diagnostic catheter, which is a major advantage of this device, especially in pediatric populations (12). However, it was not available at our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Occluding devices may be more expensive than single coils, but they are cheaper when the use of multiple items is taken into account. The advantages of these devices are their rapid deployment, their small-diameter catheter delivery systems, and their precisely targeted placement, with repositioning or removal easily achieved; device migration may still occur, however (3,4). Amplatzer devices are permanent vascular occlusion devices made of ninitol mesh and are designed to cause vessel thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on experience in peripheral and cardiac interventions, vessel occlusion devices have been used for cranial vessels [16,17]. Studies have shown effective embolization with the Amplatzer Vascular Plug used in conjunction with coils for the treatment of cavernous carotid aneurysm and pulmonary arteriovenous fistulas [18,19].…”
Section: Discussionmentioning
confidence: 99%